A candidate accident tolerant fuel system based on a highly concentrated alloy thin film. (June 2019) - Tunes, M.A.; Vishnyakov, V.M.; Camara, O.; Greaves, G.; Edmondson, P.D.; Zhang, Y.; Donnelly, S.E.
Abstract: The feasibility of depositing a thin film of highly concentrated alloy on zircaloy-4 substrates at low temperatures was investigated. Electron microscopy characterisation at micro and nanoscales showed that the deposited thin film is near-equiatomic, single-phase and with all alloying elements uniformly distributed throughout the microstructure. Heavy-ion irradiations carried out in situ within a transmission electron microscope revealed the generation of both defect clusters and inert gas bubbles at around 1.5 × 10 16 ions·cm −2 (15.4 dpa). Post-irradiation characterisation showed that the thin film preserved its solid solution and that, under the studied conditions, no elemental segregation or phase transformations were observed, indicating a high radiation tolerance. Graphical abstract: Image 1 Highlights: A highly concentrated alloy thin film was deposited on zircaloy-4. The thin film was single-phase and near-equiatomic. Alloying elements were uniformly distributed within the film microstructure. Ion irradiation in situ in a TEM was performed to assess its radiation response. At high doses, the film microstructure was preserved and defects were observed.